2011
DOI: 10.1007/s11357-011-9287-4
|View full text |Cite
|
Sign up to set email alerts
|

ApoE genotypes are associated with age at natural menopause in Chinese females

Abstract: Ages at natural menarche and menopause are influenced by several genetic factors. This study aimed to investigate the possible relationship between the apolipoprotein E (ApoE) genotype and the age at menarche and natural menopause in Chinese females. In the current study, 398 (elderly group, aged 47-80 years) and 825 (young group, aged 15-25 years) Chinese females were enrolled under informed content. Ages at natural menarche and menopause were obtained by questionnaires. ApoE genotypes were identified by rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Recently, several groups have reported the possible positive function of ApoE4 in young carriers [23–26]. We also found that ApoE4 was associated with longer reproductive period in Chinese females [27]. These evidences indicated that ApoE4 may play different role in young and elderly carriers.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, several groups have reported the possible positive function of ApoE4 in young carriers [23–26]. We also found that ApoE4 was associated with longer reproductive period in Chinese females [27]. These evidences indicated that ApoE4 may play different role in young and elderly carriers.…”
Section: Discussionsupporting
confidence: 52%
“…Other mechanisms, in addition to the one of the higher progesterone levels observed in our study, could be suggested. The presence of the ApoE4 allele was related to a later age at menopause and a longer reproductive lifespan in Chinese women [67]. Having the ApoE4 Table 2.…”
Section: Discussionmentioning
confidence: 97%
“…The APOE ε4 allele can also have an additive effect on LOAD-associated brain glucose hypometabolism (Ossenkoppele et al, 2013;Reiman et al, 2005), as this allele contributes to glucose hypometabolism even in the absence of neurodegeneration and cognitive decline (Knopman et al, 2014;Sundermann et al, 2018). As the ε4 allele is associated with delayed menopause (Meng et al, 2012), it perhaps lengthens the perimenopausal transition and worsens glucose hypometabolism. A proposed mechanism underlying ε4-associated hypometabolism is the inhibition of the PPAR-γ/PGC-1α (PPARGC1A) pathway (Box 1), which supports neuronal function by promoting mitochondrial energy production (Wu et al, 2018).…”
Section: Apoe ε4mentioning
confidence: 99%